37‐1: Development of 82‐inch Super Hi‐Vision 10K4K Liquid Crystal Display. Issue 1 (May 2016) - Huang, Yinglong; Li, Shou; Mu, Xinxin; Hu, Weipin; Liu, Sha; Bi, Yuxin; Liu, Ke; Jun, Jungmok; Liao, Yanping; Shao, Xibin
Abstract : BOE has lunched the worl's first 10K4K ultra high resolution LCD. This display has diagonal size of 82 inch and resolution of 1020 x 4 320. Its pixel density is 135 p pi. This display shows excellent characteristics, such as high color gamut, high contrast ratio and low power consumption.